2011
DOI: 10.1017/s0007114511002406
|View full text |Cite
|
Sign up to set email alerts
|

Chronic caffeine intake decreases circulating catecholamines and prevents diet-induced insulin resistance and hypertension in rats

Abstract: We tested the hypothesis that long-term caffeine intake prevents the development of insulin resistance and hypertension in two pathological animal models: the high-fat (HF) and the high-sucrose (HSu) diet rat. We used six groups of animals: control; caffeine-treated (Caff; 1 g/l in drinking water during 15 d); HF; caffeine-treated HF (HFCaff); HSu; caffeine-treated HSu (HSuCaff). Insulin sensitivity was assessed using the insulin tolerance test. Blood pressure, weight gain, visceral fat, hepatic glutathione, p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

10
115
1
2

Year Published

2012
2012
2023
2023

Publication Types

Select...
5
2

Relationship

1
6

Authors

Journals

citations
Cited by 79 publications
(128 citation statements)
references
References 59 publications
10
115
1
2
Order By: Relevance
“…We also have previously described (Conde et al 2012) that plasma concentrations of caffeine obtained with the dose 1 g/l are in the same range as those previously described in rats by Gasior et al (2002) and Cognato et al (2010) and correspond to a consumption of three to four cups of coffee per day in humans (Fredholm et al 1999).…”
Section: Discussionsupporting
confidence: 76%
See 3 more Smart Citations
“…We also have previously described (Conde et al 2012) that plasma concentrations of caffeine obtained with the dose 1 g/l are in the same range as those previously described in rats by Gasior et al (2002) and Cognato et al (2010) and correspond to a consumption of three to four cups of coffee per day in humans (Fredholm et al 1999).…”
Section: Discussionsupporting
confidence: 76%
“…Caffeine can acutely increase insulin secretion (Greenberg et al 2006), but the effects of sustained administration of the xanthine on insulin production by the pancreas appear to be, as many others, completely opposite from the ones observed after acute administration. We have previously shown that plasma insulin levels decrease after chronic caffeine treatment in hyperinsulinemic animal models of diet-induced insulin resistance (Conde et al 2012), although we could not ascertain the mechanism responsible for the lowering of plasma insulin induced by caffeine. It still remains to be clarified whether the hypoinsulinemic effect induced by chronic caffeine intake in insulin-resistant animal models is a direct effect of caffeine on the pancreas, possibly by the activation of AMPK (Long and Zierath 2006) or simply a negative feedback at the β cell ensuing improved peripheral insulin sensitivity.…”
Section: Discussionmentioning
confidence: 87%
See 2 more Smart Citations
“…Its biological half-life varies from 2.5 to 4.5 hours Caffeine stimulates insulin secretion by pancreatic β-cells by increasing intracellular Ca 2+ 7 . In skeletal muscle caffeine can increase the expression of Glucose Transporter type 4 (GLUT4) by increasing intracellular Ca 2+ concentration and AMPK expression 7,8 . Caffeine also antagonizes the adenosine receptors involved in glycogenolysis and gluconeogenesis found in the cell membranes of hepatocytes 9 .…”
mentioning
confidence: 99%